Numerical simulations of the damage evolution for plastic-bonded explosives subjected to complex stress states. (December 2019) - Liu, Ming; Huang, Xicheng; Wu, Yanqing; Chen, Chengjun; Huang, Fenglei
Highlights: The viscoplasticity is incorporated into the viscoelastic damage model ViscoSCRAM. The damage evolution is improved in the region of negative pressure. The proposed model and algorithm capture the multi-mechanism failure. Abstract: A viscoelastic–viscoplastic damage model is developed to describe the inelastic stress–strain responses and fracture processes of plastic-bonded explosives (PBXs) under complex stress states. This model improves the viscoelastic cracking constitutive model called ViscoSCRAM in two respects. (1) The growth rate factor of pressure-dependent tensile damage is incorporated into microcrack evolution equations, and the tension–compression asymmetry feature of quasi-brittle solids can be more reasonably described than the previous one. (2) The viscoplastic property, which is essential to PBXs, especially 1, 3, 5-triamino-2, 4, 6-trinitrobenzene-based explosives, is introduced into the framework through an additive decomposition of the total strain rate based on Bodner–Partom viscoplasticity. An efficient numerical scheme in the framework of large inelastic strains is developed. Several single-element tests under various loading paths and a specimen containing a cavity under compression are used to illustrate the main features and predictive capabilities of the proposed model. The numerical simulation can accurately capture the tensile cracks and diffuse shear-dominated material damage of the PBX 9502 perforated plate in comparison with the test conducted by Los Alamos National Laboratory (Liu and Thompson, 2014).